2018
DOI: 10.4236/ojanes.2017.81002
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Sedation, Hemodynamic Stability during General Anesthesia and Improving Postoperative Pain: Pregabalin Is the Answer

Abstract: Background: Tracheal intubation is a noxious stimulus that tends to provoke a marked sympathetic response which is potentially deleterious in some patients. Various methods have been used to minimize and attenuate these potentially harmful responses. Aim of the study: The present study compared the efficacy and safety of two different doses (150 mg and 300 mg) of oral pregabalin premedication on attenuation of the hemodynamic pressor response to airway instrumentation, perioperative hemodynamic stability, preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…An initial increase in heart rate was present in both the groups, however it reduced faster in the pregabalin group compared to placebo when measured at 3 and 5 minutes. The results were consistent with the study by Meena et al 17 and El-Hussiny H et al 18 where the rise of heart rate was of shorter duration in the pregabalin group. In the study done by Rastogi et al 7 , there was a significant rise in heart rate postintubation in the pregabalin group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An initial increase in heart rate was present in both the groups, however it reduced faster in the pregabalin group compared to placebo when measured at 3 and 5 minutes. The results were consistent with the study by Meena et al 17 and El-Hussiny H et al 18 where the rise of heart rate was of shorter duration in the pregabalin group. In the study done by Rastogi et al 7 , there was a significant rise in heart rate postintubation in the pregabalin group.…”
Section: Discussionsupporting
confidence: 93%
“…The haemodynamic results of our study were in agreement with the other studies. 8,18,19 A similar observation was also found by Eren et al 20 on cardiovascular response to tracheal intubation with and without pregabalin premedication. Gupta K et al 21 , however, showed an initial rise in the mean arterial after premedication but it was significantly attenuated after induction and laryngoscopy in the pregabalin group.…”
Section: Discussionsupporting
confidence: 75%
“…One could attribute this decline to the sedative effect of pregabalin. Our results could be explained by the reported dose-dependent sedative impact of pregabalin administration in clinical investigations (El-Hussiny et al 2018). The inhibitory impact of pregabalin on the release of excitatory neurotransmitters in the brain has been linked to its sedative effect (Calandre et al 2016).…”
Section: Discussionmentioning
confidence: 60%